how do i answer this question?
![how do i answer this question class=](https://us-static.z-dn.net/files/d72/8da730e5dbe522f48b2eb3d54876e328.png)
Answer:
[tex]f^{-1}[/tex] (59) = 20
Step-by-step explanation:
[tex]f^{-1}[/tex] (x) is the inverse of f(x)
to find the inverse function, let f(x) = y and rearrange to make x the subject.
y = 3x - 1 ( add 1 to both sides )
y + 1 = 3x ( divide both sides by 3 )
[tex]\frac{y+1}{3}[/tex] = x
change y back into terms of x with x = [tex]f^{-1}[/tex] (x) , then
[tex]f^{-1}[/tex] (x) = [tex]\frac{x+1}{3}[/tex] , then
[tex]f^{-1}[/tex] (59) = [tex]\frac{59+1}{3}[/tex] = [tex]\frac{60}{3}[/tex] = 20